Learning Activitiy without Interaction, is it Possible? - Ulanovskaya, I.M.; Yanishevskaya, M.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The obvious disadvantage of online education is the lack of real interaction and meaningful communication among students while solving a learning problem. We assume that under these conditions a full-fledged learning activity in its function of assimilation of theoretical concepts cannot be formed in primary school. To verify this hypothesis, we analyzed the results of meta-subject diagnostics of the fourth graders who graduated from primary school in 2015-2019 (real interaction) and graduated in 2023 (online education). 316 children in total were recruited for this study. We also used diagnostic data on meta-subject results of fifth grade students from two Moscow schools in 2019 and 2021, where "traditional" educational programs were implemented. 248 children were recruited. It is shown that the lack of conditions and opportunities for constructive interaction and meaningful communication in the process of solving learning problems complicates and slows down the development of childrens' main social competencies, but also affects other important meta-subject results of primary education. Thus, the results of meta-subject diagnostics of primary school graduates in 2023 made it possible to identify the weaknesses of online learning, its disadvantages, and to assess the consequences for the mental development of children. Главный дефицит онлайн образования - отсутствие реального взаимодействия и содержательной коммуникации учащихся в процессе решения учебной задачи. Мы предположили, что в этих условиях в начальной школе не формируется полноценная учебная деятельность, обеспечивающая усвоение теоретических знаний. Для проверки предположения были проанализированы результаты метапредметной диагностики четвероклассников, учившихся по программе развивающего обучения и закончивших начальную школу в 2015-2019 и 2023 гг. (всего 316 детей). Также использованы данные диагностики метапредметных результатов учащихся пятых классов двух московских школ 2019 и 2021 годов (всего 248 человек). Показано, что отсутствие условий и возможностей для конструктивного взаимодействия и содержательной коммуникации учащихся в процессе решения учебных задач не только затрудняет и замедляет формирование социальных компетенций, но и влияет на другие важнейшие метапредметные результаты начального образования. Таким образом, результаты метапредметной диагностики у выпускников начальной школы в 2023 г. позволили выявить слабые стороны онлайн-обучения, его дефициты и оценить их последствия для психического развития детей.